Social Piety Index for Character Development in Indonesia: A Case Study Of Mojokerto - Zainul Muhibbin; Sutikno Sutikno; Soedarso Soedarso; Imam Safawi Ahmad; Novianti Ika Sari (Institut Teknologi Sepuluh Nopember, 2022)
Since 2010, National Character Development has been a program. This nationwide initiative faces fairly significant issues due to the dynamics and changes in the life patterns of individuals. To revitalize the national program, the national movement of mental revolution was then established in 2016. This program's implementation was crucial, but it did not appear to have a precise evaluation system to measure its success. Therefore, a system of evaluation that could generate index documents of the success rate was required. Social Piety Index was the community behavior survey that had been conducted (Indeks Kesalehan Sosial-IKS). This survey examined the level of social piety and produced a document with an index of accomplishments. Consequently, the IKS record may be utilized as a depiction of the evolution of the community's character. Utilizing a quantitative approach with statistical analysis, the survey method employed was quantitative. The acquired result revealed that both the knowledge and attitude data were strong, but the level of correlation between the two was poor. The combination of a high piety index and a low correlation suggested that it was necessary to address additional concerns. These additional characteristics required specialized investigation to be revealed. The establishment of the IKS was essential, particularly if it served as an evaluation system and measuring tool for the accomplishment of national character building.